Коллекция В. А. Щавинского в истории музейного дела Украины - Борис, Тетяна Петрівна; Борис, Татьяна Петровна; Borys, Tatyana Petrivna (Санкт-Петербургский государственный университет, 2015)
Collection of the famous St Petersburg’s collector of West European Art, scientist and art critic V.O. Shchavinskyy. Collection formed during his life included pictures and engravings of the artists of the Flamish, Dutsch, Amsterdam, French and other schools, photographs of the pictures, ancient porcelain, faience, glass, books etc. In accordance with collector’s will, all his collection was descended to Kyiv, though during the revolution the part of it temporary was kept in the Hermitage. During 1925–1926 the Shchavinkyy’s collection was delivering from Petrograd to the Kyiv Art Museum of the Ukrainian Academy of sciences. V. Shchavinskyy made a great contribution in the Ukrainian history of museum affairs in the first decades of XX century connected with the establishment of national museum net, in particular central art museums В статье раскрывается собирательская деятельность известного петербургского коллекционера западноевропейского искусства, ученого и искусствоведа В. А. Щавинского. В собранную им на протяжении жизни коллекцию вошли картины и гравюры художников нидерландской, фламандской, амстердамской, французской и др. школ, фотографии картин, старинный фарфор, фаянс, стекло, книги и др. Согласно с завещанием коллекционера, все его собрание передавалось г. Киеву, хотя в период революционных событий его часть временно хранилась в Эрмитаже. На протяжении 1925–1926 гг. коллекция В. Щавинского передавалась из Петрограда в киевский Музей искусств Всеукраинской академии наук. В. Щавинский вписал важную страницу в историю музейного дела Украины первых десятилетий ХХ ст., связанных с формированием национальной музейной сети, в частности центральных художественных музеев
Collection of V. O. Shchavinskyy in the museum of Ukraine
Keywords: V. Shchavinskyy; В. Щавинский; collection; коллекция; West European Art; западноевропейское искусство; the Ukrainian Academy of sciences; Всеукраинская академия наук; Art museum; художественный музей